Construction of thought through textual (re)elaboration - Jiménez López, Guillermina; García Ruiz, María Aurora (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Writing constitutes a complex skill, since it demands a profound process of cognitive maturity and, in turn, due to its communicative nature, it needs to be informative. Likewise, through written expression, students acquire knowledge and academic and personal knowledge; therefore, it enables their cognitive development. Writing is not just a mere motor skill, it involves skills such as organization, expressiveness and creativity. We can affirm that the writing workshop represents significant learning, cooperation and fun that builds a bridge towards literature